Donas de rua, vidas lixadas : interseccionalidades e marcadores sociais nas experiências de travestis com o crime e o castigo - Ferreira, Guilherme Gomes (2018)
In the Brazilian context, it is possible to observe that, in a perspective of common sense, the category "travesti" is related to something marginal, violent, precarious, and criminal. Similarly, each day this population is more exposed to violence, a consequence, on the one hand, of a scenario of increasing social inequality and the Criminal State response towards violence and poverty and, on the other hand, of the empowerment of conservatism and rightwing political agenda. In addition to the violence that leads to travestis' deaths, we can see the selective and repressive response of the penal institution and justice system, which easily frames travestis based on productions of meaning stemming from social markers, especially gender, body, race/ethnicity, and social class. The present thesis, therefore, intends to understand how social experiences of criminalization faced by travestis, as a subaltern group, are connected to the "crime/punishment" duality: their experiences in the so-called "world of crime" and the violent socialization to which they are subjected, which makes them more easily framed by the police, in addition to their confinement byDeprivation of Liberty Institutions. The intention is to understand how these markers work to produce the prisoner and the prison itself, that is, how they contribute to the institutional and social establishment of crime as a social process towards subjects and categories of imprisonable subjects, through processes of incrimination, criminalization, subordination, and selection. We argue that these social markers emphasize and specify the process of becoming subaltern, which is expressed not only in the realm of violence, humiliation, loss of rights and all kinds of disenfranchisement, but also in the realm of disobedience, mockery, struggle and resistance.With an essentially qualitative methodology, the study encompasses an effort to triangulate data and information, from the theoretical foundation (Dialectical and Historical Materialism, intersectionality and queer studies) to sources (interviews, documents, documentaries and journalistic texts), and techniques (thematic oral history and observation for data collection, and discursive textual analysis for data handling). From the participant's life narratives collected, and the meanings theyproduced on notions such as gender identity, poverty, sex work and crime, we observe that there is a wide meaning field that is delineated from the enunciation of the word "travesti" that connects this identity to a subaltern position and violence, establishing what is understood as a precarious life: deaths that do not deserve to be grieved by the whole society, and worth that is less valuable in the process of social production and reproduction. Concerning the critical studies perspective inserted in the field of social service about subordinate relations, we observed that the reality faced by travestis expresses the historical counterevidence of the thesis, marked by the contradiction resulting from simultaneously experiencing conformism and resistance. Besides, and finally, we believe that theories of gender and sexuality, present in the foundations of a hegemonic set of social and academic movements, have not been establishing a dialogue with popular classes, or even interacting withclass perspectives in their criticisms. The thesis intends to produce a queer materialist perspective that interacts in an ethical-political, theoretical-methodological, and technical-operative way with the movements and the actual demands of these populations, highlighting the need to reverse the logic of knowledge production, which still carries a colonizer focus and an exoticism approach, and bringing to light the narratives of the interlocutors.